The Real-Fake. Issue 1 (1st December 2013) - Clarke, Rachel; Hart, Claudia
This text was written to accompany 'The Real-Fake', a touring exhibition curated in 2011 by Rachel Clarke and Claudia Hart. The show is a precursor to The New Romantics. Its purpose was to position 3D computer graphics in the discursive context of contemporary art. The artists in the exhibit all use 3D software to create a range of art forms, from the still image to animation, interactive works and installation. All of them self-consciously place 3D within an avant-garde lexicon. Like their predecessors, video artists who adapted TV technologies for artistic use, these artists adopt the technology employed in 3D shooter games and feature-length Hollywood animation blockbusters, but reject entertainment industry aesthetics and content, instead applying the medium to the trajectory of art history. 'The Real-Fake' proposed the potential of 3D computer art as the post-photographic medium currently emerging from the new technologies and Zeitgeist of the early twenty-first century.